Detecting QTL and Candidate Genes for Plant Height in Soybean via Linkage Analysis and GWAS - Wang, Jiajing; Hu, Bo; Jing, Yuliang; Hu, Xiping; Guo, Yue; Chen, Jiankun; Liu, Yuxi; Hao, Jianhui; Li, Wen-Xia; Ning, Hailong (Frontiers in Plant Science, 2022)
Soybean is an important global crop for edible protein and oil, and plant height is a main breeding goal which is closely related to its plant shape and yield. In this research, a high-density genetic linkage map was constructed by 1996 SNP-bin markers on the basis of a recombinant inbred line population derived from Dongnong L13 × Henong 60. A total of 33 QTL related to plant height were identified, of which five were repeatedly detected in multiple environments. In addition, a 455-germplasm population with 63,306 SNP markers was used for multi-locus association analysis. A total of 62 plant height QTN were detected, of which 26 were detected repeatedly under multiple methods. Two candidate genes, Glyma.02G133000 and Glyma.05G240600, involving in plant height were predicted by pathway analysis in the regions identified by multiple environments and backgrounds, and validated by qRT-PCR. These results enriched the soybean plant height regulatory network and contributed to molecular selection-assisted breeding.